Effect of Selected Plant Materials against Insect Pest Infestation of Stored Cassava (Manihot esculenta Crantaz) Chips - Sambo, Moses Emmanuel; Okrikata, Emmanuel (International Journal of Scientific Research in Biological Sciences, 2021)
Over 500 million people depend on Cassava (Manihot esculenta Crantaz) for dietary energy and research has shown that storage for just 4-6 months causes damage and losses (25-75%) due to insect pest infestations. This study is thus designed to determine the dominant insect species associated with stored cassava chips and evaluate the suppressive effect of selected plant products on pestiferous species. The study was conducted in Wukari, Nigeria (latitude 7.89N and longitude 9.77E) from January-October, 2020. The experiment consists of 5 treatments (leaves of Vernonia amygdalina, Azdirachta indica and Bombax ceiba flowers all at 100g per kg of chips; Permethrin powder at 2.0g per kg of chips and untreated control) in 4 replications of bags filled with 10 kg of cassava chips. Gallery counts were taken at 2 months interval and insect identification (including their counts and abundance) was computed at the end of the storage period. Variation in number (mean) of galleries and insects count among the treatments was compared by variance analysis after appropriate transformation. Significantly different means compared by Student Newman Keul’s Test and presented in bar charts. The relationship between pest insect count and gallery was determined by correlation and linear regression analysis. The result shows that, difference in infestation of dominant insects across treatments were significant among treatments except for R. litoralis (F=2.79, p=0.06). Untreated chips had higher number of insects (range; 9.75±4.59-13.25±3.64) while, Permethrin powder treated chips had the least number of insect counts (range; 0.50±0.50-1.75±1.03). Among the plant based treatments, A. indica had the least infestation (range; 1.00±0.71-5.50±2.72). Contrarily, B. ceiba treated chips consistently had higher presence of insects (range; 6.00±0.81-11.50±7.86). The number of galleries were positively and insignificantly (r = 0.82; p = 0.093) correlated with pest insects. Of the plant-based products used, neem leaf (A. indica) was most effective.